2005
DOI: 10.1007/s10620-005-1291-z
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease in the Turkish Population

Abstract: Celiac disease (CD) is characterized by malabsorption of nutrients in the small intestine. The availability of highly specific and sensitive serologic tests has facilitated its diagnosis, increasing the disease prevalence. The aim of this study was to determine the clinical, laboratory, and histopathological features of CD in Turkish adults. Between 1968 and 2002, CD patients presenting to the Gastroenterology Unit were evaluated retrospectively. From 2002, newly diagnosed patients were prospectively followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
1
11
0
6
Order By: Relevance
“…In (58.6%) of studied CD patients had chronic diarrhea, comparable results were present in other studies (14)(15) . In 41.4% of celiac cases in this study had normal bowel motion, Telega et al found that 28.2% of his cases had diarrhea and 5.1% had constipation suggesting that the remaining 66.7% had normal bowel motion (16) , indicating that normal bowel motion does not preclude the possibility of CD diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…In (58.6%) of studied CD patients had chronic diarrhea, comparable results were present in other studies (14)(15) . In 41.4% of celiac cases in this study had normal bowel motion, Telega et al found that 28.2% of his cases had diarrhea and 5.1% had constipation suggesting that the remaining 66.7% had normal bowel motion (16) , indicating that normal bowel motion does not preclude the possibility of CD diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…According to the results of different recently-published studies, CD affects between 1:100 and 1:200 individuals in the general population of Turkey [57]. Currently the cornerstone of the treatment is a lifelong strict gluten-free diet (GFD) [8], under which gluten is entirely eliminated from food intake and medications.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by malabsorption of nutrients by the small intestine after the ingestion of wheat gluten or related proteins from rye, oat, and barley; characteristic villous atrophy of the small intestinal mucosa, clinical and histologic recovery after a gluten-free diet (GFD), and clinical relapse after the reintroduction of gluten. 5 Intestinal mucosa contains leptin receptors, and it was postulated that direct leptin signaling in the intestine might be involved in the regulation of nutrient absorption and intestinal motility. 6,7 Furthermore, leptin is involved in immune regulation.…”
mentioning
confidence: 99%